Is food financialized? Yes, but only when liquidity is abundant - Ordu, Beyza Mina; Oran, Adil; Soytas, Ugur (Journal of Banking & Finance, 2018)
In this paper, we investigate whether commodity index trader (CIT) positions help to explain the increase in the correlations between agricultural commodities and equities starting around 2008. Some argue institutional investors who invest both in stock and commodity markets demolish the borders between these two seemingly unrelated markets and increase correlations, a recent phenomenon known as financialization. Yet, some others argue recently correlations have decreased back to historical levels and the increase between 2008 and 2012 was merely due to a business cycle effect. Our results do not support one side at the expense of the other but rather shows that both factors are important in explaining the correlations between agricultural commodities and stocks. Furthermore, we find that CITs prefer to go back to their circle of competence under scarce liquidity and thus correlations decrease back to levels absent institutions. Hence, low liquidity is a significant obstacle inhibiting financialization to occur.